A Transcriptional Repressor ZBTB1 Promotes Chromatin Remodeling and Translesion DNA Synthesis - Kim, Hyungjin (2014)
Timely DNA replication across damaged DNA is critical for maintaining genomic integrity. Translesion DNA synthesis (TLS) allows bypass of DNA lesions using error-prone TLS polymerases. The E3 ligase RAD18 is necessary for PCNA monoubiquitination and TLS polymerase recruitment; however, the regulatory steps upstream of RAD18 activation are less understood. Here, we show that the UBZ4 domain-containing transcriptional repressor ZBTB1 is a critical upstream regulator of TLS. The UBZ4 motif is required for PCNA monoubiquitination and survival after UV damage. ZBTB1 associates with KAP-1, a transcriptional repressor whose phosphorylation relaxes chromatin after DNA damage. ZBTB1 depletion impairs formation of phospho-KAP-1 at UV damage sites and reduces RAD18 recruitment. Furthermore, phosphorylation of KAP-1 is necessary for efficient PCNA modification. We propose that ZBTB1 is required for PCNA monoubiquitination, by localizing phospho-KAP-1 to chromatin and enhancing RAD18 accessibility. Collectively, our study implicates a new ubiquitin-binding protein in orchestrating chromatin remodeling during DNA repair.